Functional evaluation of complement factor I variants by immunoassays and SDS-PAGE - Gerogianni, Alexandra; Baas, Laura M.; Sjöström, Dick J.; van de Kar, Nicole C. A. J.; Pullen, Marit; van de Peppel, Siem J.; Nilsson, Per H.; van den Heuvel, Lambertus P. (Frontiers in Immunology, 2023)
Factor I (FI) is an essential regulator of the complement system. Together with co-factors, FI degrades C3b, which inhibits further complement activation. FI genetic mutations are associated with pathological conditions like age-related macular degeneration and atypical hemolytic uremic syndrome. Here, we evaluated eight recombinant FI genetic variants found in patients. We assessed FI's co-factor activity in the presence of two co-factors; Factor H and soluble CR1. Different analytical assays were employed; SDS-PAGE to evaluate the degradation of C3b, ELISA to measure the generation of fluid phase iC3b and the degradation of surface-bound C3b using a novel Luminex bead-based assay. We demonstrate that mutations in the FIMAC and SP domains of FI led to significantly reduced protease activity, whereas the two analyzed mutations in the LDLRA2 domain did not result in any profound changes in FI's function. The different assays employed displayed a strong positive correlation, but differences in the activity of the genetic variants Ile55Phe and Gly261Asp could only be observed by combining different methods and co-factors for evaluating FI activity. In conclusion, our results provide a new perspective regarding available diagnostic tools for assessing the impact of mutations in FI.